Literatura, formação de leitores e mediadores de leitura: - Cruz, Vanessa Rita de Jesus (2023)
The general objective of this research, Literature, formation of readers and reading mediators: João Vítor, a reader character, is to think about literature, the reader, the formation of readers and mediation, notions dear to the school, from the work Odyssey by Homer (according to João Vítor), by Gustavo Piqueira. We will carry out a theoretical and analytical path, considering the importance of literature; the mediation spaces and the pertinence of the work of reading mediators, especially teachers, which requires thinking, including, about their training; the public policies that thought and think about the formation of readers; the importance of valuing subjectivity in the formation of the reader and the place of canonical and adapted works within the school. We argue that the encounter with the literary, through print or digital, is possible because at some point the reader found or will find a reading mediator, in the classroom, library or on social networks; the adapted texts have become an additional resource for the teacher to take the reader to the book; reading carried out under the influence of aspects related to personal experience can become an element that brings the reader even closer to the literary text, validating the subjective reading, without disregarding the importance of the student being equipped with knowledge that allows him to have a more universal reading . In this way, this research aims to contribute to the educational area, mainly to the teaching of literature, in the sense of providing a reflection on the modes of reading that permeate the daily lives of students, considering the exercise of mediation as something essential for the development of practices aimed at training readers. This is a bibliographical and theoretical research, through which we undertake a hermeneutic exercise in relation to our selected corpus, Homer's Odyssey (according to João Vítor), by Gustavo Piqueira. In order to reach our objective and base our theoretical and critical considerations, we resorted to several authors, in order to offer theoretical support and also subsidize the methodological proposal. In this sense, with regard to the analysis of our corpus, we resort to adaptation considerations by Álvaro Hattnher (2010, 2013), admiration of great works and authors by Houdart-Mérot (2013) and reading horizons by Hans Robert Jauss (2002). With regard to the relationship between literature and school, as theoretical support we used Maria Luisa Santos Ribeiro (2003), Regina Zilberman (1988, 2003, 2011 and 2016), Teresa Colomer (2007), Nelly Novaes Coelho (2000) , Rildo Cosson (2011 and 2021), Neide Luzia de Rezende (2018), Magda Soares (2002 and 2011), Jorge Larrosa (2010), Marisa Lajolo (2000). With regard to the theoretical subsidy on public policies aimed at the book and the reader, we are based mainly on Flávia Goullart Mota Garcia Rosa and Nanci Oddone (2006) and Jaqueline de Grammont (2005). Regarding teacher training, we turned to Bernadete A. Gatti (2010), Regina Zilberman (1988), Luiza Helena Oliveira da Silva (2017), Márcio Araújo de Melo and Luiza Helena Oliveira da Silva (2018) and Josalba Fabiana dos Santos ( 2021). With regard to the subjective reading, we turn to the studies of Annie Rouxel, Gérard Langlade and Neide Luzia de Rezende (2013) and Vincent Jouve (2013). The foundation on reader was based on Antoine Compagnon (2009 and 2010), Umberto Eco (2003 and 2004), Terry Eagleton (2019), Marcel Proust (2011) and Ricardo Piglia (2006). Other authors, researches and relevant sites were read and visited for the accomplishment of our work. Gustavo Piqueira's text allowed us to analyze and reflect on how much the training process of literary readers is influenced by issues ranging from the choice of the work to be read and its motivation, access to the book, the objective by requesting the reading, the necessary mediation to carry out the reading, to the extent to which the reader can be